Production of Carotenoids-rich Palm Olein by Supercritical Fluid Extraction - C.W, Puah; Y.M, Choo; A.N, Ma; C.H, Chuah (Malaysian Journal of Science (MJS), 2006)
A carotenoids-rich palm olein of nutritional attributes is obtained using supercritical fluid extraction. It contains >1000 ppm of carotenoids with >99% of triacylglycerols. The partial acylglycerols (mono- and diacylglycerols) are <1.0% and a non-detectable amount of free fatty acids using GC-FID. The palm olein also contains vitamin E with 350 ppm. The carotenoids-rich palm olein has lower cloud point of 7.8°C compared to commercial oil. The study was carried out with low temperature of 40°C and gradient pressures of 14 MPa to 30 MPa. A comparative study of the quality of the supercritical fluid extraction produced palm olein with commercial refined, bleached and deodorised palm olein was performed. Results of the study showed that the quality of the carotenoids-rich palm olein was comparable with the commercial olein. This study shows that supercritical fluid extraction is a potential technology for refining of crude palm oil.